Concilium Universale Nicaenum secundum: Concilii Actiones I–III. Edited by Erich Lamberz - Tanner, Norman (The journal of theological studies, 2009)
This welcome volume inaugurates the final stage of the monumental work initiated by E. Schwartz. Of the first two ecumenical councils of the Christian church, Nicaea I in 325 and Constantinople I in 381, only the decrees (creeds and/or canons) that were promulgated by the councils, and a few other relevant documents, are known. No acta (minutes of the conciliar proceedings) have come down to us; whether they ever existed is unclear. Thereafter, beginning with the council of Ephesus in 431, such acta survive in abundance.